Readiness of the Religious Affairs Office, Sambeng District, Lamongan Regency to Manage Dynamic Archives: What are the Implications for Office Management? - Ernawati, Ernawati (Universitas Negeri Surabaya, 2024)
Ineffective archive management affects employee performance, emphasizing the need for proper facilities and skills. This study examines archive management practices, challenges, and solutions at the Religious Affairs Office, Sambeng District, Lamongan Regency. This study used descriptive qualitative approach. Subjects were two administrative staff and one general functional staff member. Data were collected through semi-structured interviews, observation, and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions using data validation techniques in the form of triangulation. Data showed that the archives management at the Sambeng District Religious Affairs Office could have been more optimal, because there was no recording of incoming letters in the agenda book. There are no archivists, so all employees have the task of managing archives. There were obstacles in carrying out administrative activities because the storage process was carried out by different people, resulting in difficulties when rediscovering archives. Infrequent shrinkage results in documents piling up, resulting in inadequate storage space. However, the employees consistently serve the community well and as fully as possible. Apart from that, employees also try to overcome the obstacles to create more optimal service, namely public satisfaction with the services provided.